Compact Inverted C shaped Monopole Antenna for C-band Applications - Patel, Mahima; Verma, Shudhanshu; Khalid, Saifullah (2020 International Conference on Electrical and Electronics Engineering (ICE3), 2020)
This paper presents compact C shaped microstrip feed line with C and Inverted T slots antenna (CITSA) applicable for satellite communication. This preferred antenna has simple geometry as compare to other antennas which are designed for realize wide band impedance characteristics. It contains C shaped microstrip feedline, C and Inverted T slots at partial ground and patch respectively and FR4 epoxy substrate. The antenna design simulation performance validated on HFSS. The size of proposed antenna 30× 30× 1.6\ \text{mmm}^{3} . The impedance bandwidth of antenna is 71.28% (4-8.43 GHz) centered at 4.6GHz and 6.8GHz. The average peak gain of antenna is 2.55dB. It has 98% radiation efficiency.